Uji Aktivitas Antioksidan Ekstrak Etanol Batang Daun dan Bunga Jumpai (Glinus oppositifolius (L.) Aug. DC.) - Astuti Amin; Andi Paluseri; Rahmat Priyandi Linggotu (Jurnal Kimia Fullerene, 2021)
Jumpai (Glinus Oppoitifolius (L.) Aug. DC) contains flavonoids compounds that can act as antioxidants by donating hydrogen so as to stabilize the lack of electrons in free radicals. This study aims to determine the antioxidant potential of stem, leaf, and flower extracts by looking at the IC50 value. The stems, leaves, and flowers were extracted by maceration using 70% l ethanol solvent. The results of the antioxidant activity test using the DPPH method (2,2-diphenyl-1-picrilhydrazil) showed very strong antioxidant activity with IC50 values of 9.523 µg / ml stem, 32.89 µg / ml leaves, and 23.07 µg / ml flowers with vitamin comparisons. C obtained IC50 value of 1,698 µg / ml. Based on these results, it can be rejected that the stems, leaves, and flowers have antioxidant activity with a very strong category against DPPH free radicals (2,2-diphenyl-1-picrilhydrazil).